The parabrachial nucleus: CGRP neurons function as a general alarm - Palmiter, Richard D. (Trends Neurosci, 2018)
The parabrachial nucleus (PBN), which is located in the pons and dissected by one of the major cerebellar output tracks, is known to relay sensory information (visceral malaise, taste, temperature, pain, itch) to forebrain structures including the thalamus, hypothalamus and extended amygdala. The availability of mouse lines expressing Cre-recombinase selectively in subsets of PBN neurons and of Cre-dependent viruses that allow circuit mapping and manipulation of neuron function is beginning to reveal the connectivity and functions of PBN’s component neurons. This review focuses on the PBN neurons that express calcitonin gene-related protein (CGRP(PBN)) that play a major role in regulating appetite and transmitting real or potential threat signals to the extended amygdala. The functions of other specific PBN neuronal populations are also discussed. This review aims to encourage investigation of the numerous unanswered questions that are becoming accessible.